The last chance christmas ball ebook - Putney, Mary Jo (2015)
Christmas 1815. Upstairs and downstairs, Holbourne Hall is abuzz with preparations for a grand ball to celebrate the year's most festive--and romantic--holiday. For at the top of each guest's wish list is a last chance to find true love before the New Year... A chance meeting beneath the mistletoe, a stolen glance across the dance floor--amid the sumptuous delicacies, glittering decorations, and swell of the orchestra, every duchess and debutante, lord and lackey has a hopeful heart. There's the headstrong heiress who must win back her beloved by midnight--or be wed to another....the spinster whose fateful choice to relinquish love may hold one more surprise for her...a widow yearning to glimpse her long-lost love for even one sweet, fleeting interlude ...a charming rake who finds far more than he bargained for. And many other dazzling, romantic tales in this star-studded collection that will fill your heart and spice up your holidays...